EXPORT POTENTIAL OF BUSINESS ENTITIES IN MEDICAL INSTITUTIONS AND STATE SUPPORT FOR EXPORT ENTERPRISES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article analyzes additional measures aimed at providing state support and increasing the export potential of business entities in medical institutions operating in our country, with the aim of further developing medical and health tourism in the Republic of Uzbekistan. Accordingly, the article analyzes the medical tourism service program, as well as the system for monitoring the quality of services provided by medical institutions, sanatoriums, and boarding houses, the creation of medical tourism clusters and the implementation of incentive mechanisms, the development of a medical and health tourism brand and its ongoing promotion, the creation of star-rated sanatoriums and the implementation of a certification system for them, and other issues planned for implementation within the framework of state programs.